Patients help other patients: Qualitative study on a longstanding community cooperative to tackle leprosy in India - Jung, Seong Hye; Han, Hee Won; Koh, Hyeonseok; Yu, Soo-Young; Nawa, Nobutoshi; Morita, Ayako; Ong, Ken Ing Cherng; Jimba, Masamine; Oh, Juhwan (PLOS Neglected Tropical Diseases, 2020)
Although leprosy is portrayed as a disappearing disease, leprosy affected persons in India are still suffering massively. Even further, nearly 60% of the world's newly detected cases are appearing from India alone. The problem has exacerbated due to the drastic decrease of global funding after India's official declaration of 'elimination', which did not foster the actual pain of patients beyond prevalence. Leprosy patients have hardships in their lives due to disabilities, stigma and poverty; thus, they require sustained, continuous care even after release from treatment. Yet, current interventions mostly have a vertical, short-term approach, not showing much progress in lightening the burden of leprosy. In contrast, Little Flower Hospital Community (LFHC) in India has been remarkably providing holistic care for thousands of leprosy patients for 35 years. However, there has not been any research conducted to uncover the underlying factors of this longstanding leprosy control model. Therefore, this research explores the in-depth contextual attributes of this hospital community that has been able to successfully provide sustainable care for a long time even without excessive external funds. This qualitative research used a grounded theory approach, involving 28 in-depth interviews of 11 patients, 13 workers, and 4 board members from the hospital. The interview data were inductively analyzed to examine the contextual factors of the hospital's sustainability. Open coding, axial coding and selective coding were conducted, and Glaser's Six C's model was used to create a theoretical model of the sustainability of LFHC. The fundamental cause of the sustainability was the leprosy patients' strong craving for life with dignity, despite the isolation from the society. The desire resulted in a bottom-up formation of a 'consumer-provider cooperative', where patients mutually support each other with basic treatment learned from experience. The profits earned from the patients' occupational efforts such as dairy farming, cover the costs needed to manage the hospital community, which contributes to economical sustainability. Social sustainability was established through the holistic care including psychosocial, educational, medical, and residential support. The wholesome care socially rehabilitated the patients to be included in the society with satisfaction, social justice and social cohesion. The main limitation of this study is that this study cannot be generalized due to the nature of Grounded Theory based study. This study investigated the determinants that made LFHC sustainable, and the findings suggested the importance of forming a cooperative community and implementing social rehabilitation for sustainable leprosy control. More exploration on transferring this model to other leprosy colonies will have great impact in maintaining sustainable care for leprosy patients. Furthermore, this research may highlight the importance of sustainable development in policies targeting neglected tropical diseases beyond leprosy as well.